Schem@Doc: a web-based XML schema visualizer - Leal, José Paulo (2014)
XML Schema is one of the most used specifications for defining types of XML documents. It provides an extensive set of primitive data types, ways to extend and reuse definitions and an XML syntax that simplifies automatic manipulation. However, many features that make XML Schema Definitions (XSD) so interesting also make them rather cumbersome to read. Several tools to visualize and browse schema definitions have been proposed to cope with this issue. The novel approach proposed in this paper is to base XSD visualization and navigation on the XML document itself, using solely the web browser, without requiring a pre-processing step or an intermediate representation. We present the design and implementation of a web-based XML Schema browser called schem@Doc that operates over the XSD file itself. With this approach, XSD visualization is synchronized with the source file and always reflects its current state. This tool fits well in the schema development process and is easy to integrate in web repositories containing large numbers of XSD files.